Postnatal Feeding With a Fat Rich Diet Induces Precocious Puberty Independent of Body Weight, Body Fat, and Leptin Levels in Female Mice - Ullah, Rahim; Raza, Ali; Rauf, Naveed; Shen, Yi; Zhou, Yu-Dong; Fu, Junfen (Frontiers in Endocrinology, 2019)
Puberty generally occurs when an individual has stored a sufficient amount of energy. Previous reports have shown that postnatal overfeeding, induced by a small litter size or maternal high fat diet (HFD) feeding during gestation and lactation increases body weight (BW), body fat, plasma leptin levels, and induces precocious puberty. The role of BW, body fat, and leptin in postnatal HFD-induced precocious puberty is poorly understood. In this study, we investigated if postnatal HFD feeding induces precocious puberty independent of BW, body fat, and leptin levels. Different litter sizes and different exposure time to HFD were used to produce HFD feeding pups with different BW and body fat. BW, body fat, and plasma hormones levels were checked at different time points to test their relation with HFD-induced precocious puberty. Our results showed that postnatal HFD feeding increases BW, body fat, adipocyte size, and induces precocious puberty. HFD-induced precocious puberty was independent of BW, body fat, and plasma leptin levels. Plasma gonadotrophin, estradiol, testosterone and insulin levels were comparable in most of the groups. Our results collectively suggest that postnatal HFD feeding induces precocious puberty independent of BW, body fat and plasma leptin levels. Our results also suggest that HFD feeding acts as a stimulator for puberty onset but further studies are needed to understand how it induces precocious puberty.